Increasing electric vehicle hosting capacity and equality for fast charging stations using residential photovoltaics in medium‐ and low‐voltage distribution networks. Issue 3 (2nd December 2019) - Sugihara, Hideharu; Funaki, Tsuyoshi
Abstract : To achieve broad installation of electric vehicles (EVs), it is important to deploy fast EV charging stations at many points without distribution network reinforcement. This study develops a methodology for evaluating the hosting capacity for fast EV charging loads under medium‐ and low‐voltage (MV and LV) distribution networks with bus‐voltage and line‐current constraints; hence, the promising combination of fast EV charging and rooftop photovoltaic (PV) generation in distribution networks is analyzed. In particular, on a sunny day, the active power output supplied by rooftop PVs can be used to mitigate the voltage drop problem for end‐use residential customers. On a cloudy day, even though the active power output is smaller, the residual inverter capacities of rooftop PVs can be used to generate reactive power from those systems. In addition, in order to evaluate the spatial equalization of the EV hosting capacity at fast charging stations, an equalization factor of the spatial distribution is proposed, which is obtained as a percentage of the EV hosting capacity in the equally maximized case over that in the simply maximized case. The equalization factor can be improved from approximately 33 to 70% using the active and reactive power outputs from residential rooftop PVs. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.